Genome-wide Mapping and Characterization of Notch-Regulated Long Noncoding RNAs in Acute Leukemia - Trimarchi, Thomas; Bilal, Erhan; Ntziachristos, Panagiotis; Fabbri, Giulia; Dalla-Favera, Riccardo; Tsirigos, Aristotelis; Aifantis, Iannis (Cell, 2014)
Notch signaling is a key developmental pathway that is subject to frequent genetic and epigenetic perturbations in many different human tumors. Here we investigate whether long noncoding RNA (lncRNA) genes, in addition to mRNAs, are key downstream targets of oncogenic Notch1 in human T cell acute lymphoblastic leukemia (T-ALL). By integrating transcriptome profiles with chromatin state maps, we have uncovered many previously unreported T-ALL-specific lncRNA genes, a fraction of which are directly controlled by the Notch1/Rpbjκ activator complex. Finally we have shown that one specific Notch-regulated lncRNA, LUNAR1, is required for efficient T-ALL growth in vitro and in vivo due to its ability to enhance IGF1R mRNA expression and sustain IGF1 signaling. These results confirm that lncRNAs are important downstream targets of the Notch signaling pathway, and additionally they are key regulators of the oncogenic state in T-ALL. [Display omitted] •Many previously unreported lncRNA genes are expressed in human T-ALL•Notch1 oncogene directly controls lncRNA expression in T-ALL•LUNAR1 is a Notch-regulated pro-oncogenic lncRNA that is essential for T-ALL growth•LUNAR1 maintains high expression of IGF1R mRNA through a cis-activation mechanism Manual annotation of lncRNA genes revealed many previously unreported T-ALL-specific lncRNAs. A Notch-regulated lncRNA, LUNAR1, controls the expression of the IGF1R gene through chromosomal looping and thereby IGF1 signaling and growth of T-ALL.